Холостая война: художественная лит-ра / С. И. Зверев - Зверев Сергей Иванович (Спецназ, 2013)
Экземпляры: ф.14 (20141205) / Инвентарный номер: 51229 / Цена: 40. 00. / Сис.шифр: Р2 / Авт.знак: З-43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4